The The Relationship Between Internet Addiction and Academic Procrastination in Nursing Bachelor Students Who Are Compiling Thesis in Bandung - Nurmansyah, Andri; Fauziah, Fifi Siti; Supriadi, Dedi; Tauba, Ahmad Mumtaz (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Academic procrastination is a widespread issue affecting university students, often linked to behavioral factors such as uncontrolled internet use. Among final-year nursing students, extended time spent on non-academic online activities—exceeding four hours daily—may contribute to delays in completing academic responsibilities. Objective: This study aimed to explore the relationship between internet addiction and the tendency to procrastinate academically among undergraduate nursing students. Method: A correlational quantitative approach was utilized in this study. The target population included 90 final-year students, with 86 respondents selected using an accidental sampling method. Data were collected through two standardized questionnaires—one measuring internet addiction levels and the other assessing academic procrastination. Statistical analyses included both univariate and bivariate procedures, with Spearman's rank correlation used to examine the association between the two variables. Results: Of the 86 participants, 60 students (69.8%) demonstrated moderate internet addiction, while 56 students (65.1%) reported moderate levels of academic procrastination. Analysis showed a statistically significant positive correlation between internet addiction and procrastination behavior (p = 0.007; r = 0.288). These findings suggest that higher levels of internet dependency are associated with an increased likelihood of delaying academic tasks. Conclusion: There is a meaningful association between excessive internet use and academic procrastination. It is recommended that students develop better time management strategies by limiting recreational internet use and allocating focused periods for academic work to reduce procrastination tendencies and improve academic outcomes.